Understanding creative teaching in twenty-first century learning among Islamic education teachers during the COVID-19 pandemic - Zulkifli, Hafizhah; Tamuri, Ab Halim; Azman, Nor Alniza (Frontiers in Psychology, 2022)
Education in the midst of COVID-19 pandemic requires teachers to be creative because students will not be able to complete education in a normal way. However, Islamic education teachers seem to lack the skills and attitude in the 21st century learning causing creative teaching not to be carried out properly. Thus, the purpose of this study is to understand how Islamic education teachers teach creatively in the 21st century learning during the COVID-19 pandemic. Qualitative methodology was employed through the case study design. The sample consisted of four Islamic education teachers who teach in Putrajaya schools. The findings illustrated that there were six themes for creative teaching consisting of student-centered learning, 21st century teaching, synchronous and asynchronous, creative inspirations, creative recipe, creative activities and one theme for assessment namely alternative evaluation. This study grants Islamic education teachers to be creative in teaching and enhance the professional development of Islamic education teachers respectively.